Nitric oxide counteracts cytotoxic processes mediated by reactive oxygen species in plant tissues - Beligni, M.V; Lamattina, L (Planta, 1999)
Many environmental conditions subject plants to oxidative stress, in which reactive oxygen species (ROS) are overproduced. These ROS act as transduction signals in plant defense responses, but also cause effects that result in cellular damage. Since nitric oxide (NO) is a bioactive molecule able to scavenge ROS, we analyzed its effect on some cytotoxic processes produced by ROS in potato (Solanum tuberosum L. cv. Pampeana) leaves. Two NO donors: (i) sodium nitroprusside and (ii) a mixed solution of ascorbic acid and NaNO(2), were able to prevent chlorophyll loss mediated by the methyl viologen herbicide diquat (a ROS generator), with effective concentrations falling between 10 and 100 micromolar of the donors. This protection was mimicked by thiourea and penicillamine, two antioxidant compounds. Residual products from NO generation and decomposition failed to prevent chlorophyll decline. A specific NO scavenger, the potassium salt of 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline -1-oxyl-3-oxide (carboxy-PTIO), arrested NO-mediated chlorophyll protection. In addition, some events mediated by ROS during infection of potato leaves with Phytophthora infestans (race 1, 4, 7, 8, 10, 11, mating type A2) were also examined. In this sense, NO proved to markedly decrease ion leakage and the number of lesions, indicative of cell death, produced upon infection in potato leaves. The NO-mediated decrease in ion leakage was also inhibited by carboxy-PTIO. Fragmentation of DNA diminished when P. infestans-infected potato leaves were treated with 100 micromolar SNP. These results suggest that, acting as an antioxidant, NO can strongly counteract many ROS-mediated cytotoxic processes in plants. Moreover, the evidence of NO functionality in the plant kingdom is strengthened by this work.